Circus is a performance but it is also a building—memory of circus buildings in Europe - Marija Divac (City, Territory and Architecture, 2022)
Abstract Circus spectacle, its architectural concept and its content, has changed throughout the centuries, following social events and cultural frameworks of time periods. In this research paper, we investigate the history of circus in Europe which occurred in between the eighteenth century and today’s twenty-first century. The evolution of circus gradually took place and could be followed through the modifications in forms of the buildings in different cities of the continent. Firstly, we research their stationary architecture which establishment is just over in this period. Even though the performance is still changing and modifying, it is questionable if the stationary circuses achieved in adjusting and transform for the purposes of modern society or, on the other hand, they are reorganized in their function and are becoming something completely different.